2015
DOI: 10.5433/1679-0359.2015v36n4p2407
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento e nutrição de mudas de abacaxizeiro ‘Imperial’ associadas com o fungo Piriformospora indica e aplicação de herbicidas

Abstract: A baixa oferta de mudas sadias e com qualidade tem sido um obstáculo para o crescimento da abacaxicultura no Brasil. A pesquisa foi realizada com o objetivo de avaliar a associação micorrízica, o crescimento e absorção de nutrientes em mudas micropropagadas de abacaxizeiro 'Imperial' inoculadas com o fungo Piriformospora indica em cultivo com a aplicação de herbicidas. Foi utilizado o esquema fatorial 2 x 4, sendo os fatores duas inoculações: mudas inoculadas com o fungo P. indica e sem inoculação e quatro dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For magnesium, there were no statistical differences regarding organic sources and use of the hydrogel for the two cultivars. In addition, the average values presented in this work for leaf calcium and magnesium contents were lower than those considered suitable by nutritional studies with pineapple seedlings during the acclimatization stage (Teixeira et al, 2009;Baldotto et al, 2009;Leonardo et al, 2013;Ramos et al, 2011;Cruz et al, 2015).…”
Section: Cultivarsmentioning
confidence: 91%
See 2 more Smart Citations
“…For magnesium, there were no statistical differences regarding organic sources and use of the hydrogel for the two cultivars. In addition, the average values presented in this work for leaf calcium and magnesium contents were lower than those considered suitable by nutritional studies with pineapple seedlings during the acclimatization stage (Teixeira et al, 2009;Baldotto et al, 2009;Leonardo et al, 2013;Ramos et al, 2011;Cruz et al, 2015).…”
Section: Cultivarsmentioning
confidence: 91%
“…Fagundes et al (2015), studying a water absorbing polymer for the reduction of nutrients leached during the production seedlings of yellow passion fruits, found that N losses by leaching decreased as the dose of the polymer increased: there was a decrease of 47.8% on the leached material of a Bioplant ® substrate and a decrease of 33.4% on a Provaso ® substrate during the evaluation of nutrients.…”
Section: Cultivarsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cayenne and Champaka produced similar biomass and MD2 a little less than these two cultivars, which can be explained because Champaka is a pure clone obtained from Cayenne. MD2 is a hybrid obtained from a different phylogenetic group, and its management is highly demanding of nutrients, mainly K, due to its fast growth and is very susceptible to fungal attack (Barreto-Cruz et al, 2015;Valleser, 2019). Excessive fertilizer applications in f ield production and tested in this work under greenhouse conditions proves again that high P quantities reduce AMF development, as reported in previous research (Balzergue et al, 2011), and in these pineapple cultivars may even cause crop growth depressions.…”
Section: Discussionmentioning
confidence: 99%